Nitrogen fixation in the rhizosphere of Paspalum notatum and sugar cane - Döbereiner, Johanna; Day, John M.; Dart, Peter J. (Pesquisa Agropecuaria Brasileira, 2014)
Nitrogen fixation in the rhizosphere of Paspalum notatum, variety “Batatais”, associated with Azotobacter paspali and sugar cane associated with Beijerinckia sp., both grown in the field, was studied by the acetylene reduction method. In the association P. notatum - A. paspali values equivalent to a Nitrogen fixation of 15 to 93 kg/ha/year were obtained (ratio C2H2:N2 = 3:1). Almost all of the nitrogenase activity was concentrated on the root surface and very little was found in rhizosphere soil. Nitrogenase activity of both systems was very sensitive to oxygen. On roots separated from soil a pO2 of 0.04 atm was optimal while in the intact systems the oxygen tension above the soil had little effect. Nitrogenase activity in the rhizosphere of P. notatum seemed directly dependent upon photosynthetic activity of the plant. Normal 8 hour night periods did not change nitrogenase activity but when the dark period was extended the activity slowed down. On returning the plants into light, within hours the original activity was reached.